The Effect of Ownership Structure and Corporate Social Responsibility on Financial Performance and Firm Value in Mining Sector Companies in Indonesian - Fadrul Fadrul; Budiyanto Budiyanto; Nur Fadjrih Asyik (International Journal of Economics Development Research (IJEDR), 2021)
This study is intended to examine the effect of institutional ownership, managerial ownership, and CSR on financial performance (Model I). This study also conducted tests related to the effect of institutional ownership, managerial ownership, CSR, and financial performance on firm value (Model II). The population used is 39 mining sector companies with a sampling technique using a saturated sample technique. Data analysis was carried out using path analysis techniques with the help of SPSS. The results show that institutional ownership and CSR have a significant effect on financial performance, while managerial ownership has no significant effect on financial performance. Institutional ownership, managerial ownership, CSR, and financial performance were found to have a significant effect on firm value. In addition, financial performance is proven to be able to partially mediate the effect of institutional ownership and CSR on firm value.